French-Russian Academic Conference “Economy, Policy and Society: New Challenges and Prospects”. Workshop “Economics of S&T and Innovation” - Нет, Нет (Foresight and STI Governance, 2011)
The review summarizes discussions held in the framework of the workshop «Economics of S&T and Innovation» as a part of the French-Russian Conference “Economy, Policy and Society: New Challenges and Prospects” (Higher School of Economics, Moscow, 28-29 October, 2010). The participants became acquainted with the results of studies implemented in Russia and France that reflected new approaches to measuring S&T and innovation performance and to analysing human capital of S&T.